Role of Environmental Factors in Cocaine Addiction - Badiani, Aldo; A. Spagnolo, Primavera (Current Pharmaceutical Design, 2013)
Decades of experimentation with a variety of pharmacological treatments have identified some effective therapies for heroin addiction but not for cocaine addiction. This may be due, at least in part, to our incomplete understanding of the factors involved in the differential vulnerability to these addictions, which are often considered mere variations of the same disorder. Indeed, the preference for one drug or another has been variously attributed to factors such as drug availability or price, to the addict’s lifestyle, or even to chance. Yet, there is evidence of substance-specific influences on drug taking. Data from twin registries, for example, suggest that a sizeable portion of the variability in the susceptibility to drug abuse is due to environmental factors that are unique to opiates or to psychostimulants. Very little is known about the nature of these environmental influences. We report here original data, based on retrospective reports in human addicts, indicating that the setting of drug taking exerts a differential influence on heroin versus cocaine use. We also review additional clinical and pre-clinical data pointing to fundamental differences in the way in which the environment interacts with cocaine relative to heroin and other addictive drugs. These findings - as well as other evidence, including the lack of pharmacological treatments effective for both cocaine and heroin addiction - support the notion that much is to be gained by taking into account the substance-specific aspects of drug addiction. At a therapeutic level, for example, it appears reasonable to propose that cognitive-behavioral approaches should be tailored in a substance-specific manner in order to allow the addict to anticipate, and cope with, the risks associated to the various environmental settings of drug use.
Keywords: Environment